Konstruktion av nya nödskorstenslock - Bolin, Rasmus (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2022)
This is a thesis for bachelor’s degree in mechanical engineering at Luleå tekniska universitet. Containing a redesign of existing emergency chimney caps places on the radiation chamber, which is part of the exhaust gas cleaning process after electronic scrap combustion in the E-kaldo plant at Boliden Rönnskär in Skelleftehamn.The task of the emergency chimney cap is to release overpressure and be an extra safety in the event of explosions in the radiation chamber. This emergency chimney caps today requires a great deal of maintenance due to both heat related deformations and corrosion. This has led to modifications of the emergency chimney lids which have made it possible to maintain the process for the E-kaldo plant. The result of the modifications is that the opening pressure for the emergency chimney cap has increased. The original version of the emergency chimney caps consisted of two more or less identical lids that stood near each other and these were built with EN 1,4547 sheet metal. The lower part of each individual emergency chimney cap was welded together as a slightly raised square box above the radiation chamber. On top of the lower part was a lid recessed. The lid was also made with welded plates of the same material. Inside the wall of the box and in the caps was a refractory mortar. From the beginning, it had a water trap as a gas seal between the lid and the lower part. A lifting arm in S355 carbon steel equipped with hydraulics lifted and closed the lids in case it should be opened manually. The lifting arm was equipped with counterweights that regulate the opening pressure on the emergency lids. In case of emergency, the lids open slightly without affecting the hydraulics. In the event of explosions in the radiation chamber, a pressure valve in the hydraulic system will be exceeded and the lids will be fully opened. The advice is that the lifting arm is reintroduced with various minor adaptations and that the materials continue to be recommended for the purpose. The sheet metal lids are ...